Enhancing safety: when domestic violence cases are in multiple legal systems (criminal, family, child protection) : a family law, domestic violence perspective - Neilson, Linda C. (Family, Children and Youth Section, Department of Justice Canada, 2013)
"The purpose of this report is to document, from a family law perspective, best practice options when domestic violence cases are making their way through multiple proceedings (criminal, civil, family, and child protection). The intention is to identify practices that can promote the safety of family members, particularly children, while also ensuring fair, due process"-- Executive summary.